2014
DOI: 10.1002/jca.21358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plateletpheresis on the Fenwal Amicus, Fresenius COM.TEC, and Trima Accel Cell separators

Abstract: Blood component donations by apheresis have become more common in modern blood transfusion practices. We compared three apheresis instruments (Fenwal Amicus, Fresenius COM.TEC, and Trima Accel) with regard to platelet (PLT) yield, collection efficiency (CE), and collection rate (CR). The single-needle or double-needle plateletpheresis procedures of the three instruments were compared in a retrospective, randomized study in 270 donors. The blood volume processed was higher in the COM.TEC compared with the Amicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…The median actual PLT yield in our donors was 5.96 × 10 11 . This finding is comparable to other reports in which PLT yields collected by Trima Accel cell separator varied between 4.5 × 10 11 and 7.48 × 10 11 . Almost all of our concentrates (97.36%) met the AABB criteria, which establishes that 75% of the single donor products must contain ≥ 3 × 10 11 PLTs, while all of them had ≥ 2 × 10 11 PLTs per unit, meeting the European guidelines, thus validating Trima v6.0 performance.…”
Section: Discussionsupporting
confidence: 88%
“…The median actual PLT yield in our donors was 5.96 × 10 11 . This finding is comparable to other reports in which PLT yields collected by Trima Accel cell separator varied between 4.5 × 10 11 and 7.48 × 10 11 . Almost all of our concentrates (97.36%) met the AABB criteria, which establishes that 75% of the single donor products must contain ≥ 3 × 10 11 PLTs, while all of them had ≥ 2 × 10 11 PLTs per unit, meeting the European guidelines, thus validating Trima v6.0 performance.…”
Section: Discussionsupporting
confidence: 88%
“…Existing blood cell separators apply the principle of gradient density difference; however, minimal density difference between each blood component (1.6–2.2%) 17 20 , and different blood cells in terms of volume and density has certain degree of overlap, so there are large platelets and red blood cell contaminated in leucocytes in the process of leukapheresis in clinic. A large number of platelets lost by patients in a short time resulted in a significant increased risk of late chemotherapy and delayed the opportunity for better treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Donor demography, hematological values & procedural factors in platelet pheresis (n=1455)MCS+in the current study, Tendulkar and Rajadhyaksha observed anticoagulant use with the Cobe compared to Amicus10 . In another study by Keklik et al, the Trima and Amicus were comparable with regard to all parameters, except PLT yield and collection efficiency which was better with the Trima compared to Hemonetics MCS+11 .…”
mentioning
confidence: 79%